NATO's Northern Flank: A Critique of the Maritime Strategy - Hooker, Jr, Richard D. (1989)
For most of this decade, naval enthusiasts have championed the "Maritime Strategy" as the answer to the strategic malaise that characterized American foreign policy in the post-Vietnam era. Perceived American weakness and strategic incoherence undoubtedly contributed to the burst of Soviet adventurism beginning in Angola in 1974 and culminating most spectacularly with the invasion of Afghanistan in 1979. Yet the large military expenditures of the last seven years. which were intended to reverse the declining "correlation of forces" and reestablish US military power as an effective instrument of policy, were not rigorously submitted to the discipline of an articulated and integrated conception of national military strategy. In the scramble for defense resources each service advanced its own interests, but the sea services emerged clear winners, basing their requests for funds on the strategic necessity for a modernized, offensively oriented, greatly enhanced naval force structure. In the process, the Navy has largely succeeded in independently defining and marketing the very strategic framework by which its budget requests are evaluated. A case in point is the wartime defense of NATO's critical Northern Flank. Navy strategy there is bold, aggressive, and dynamic in every way. It may also be a prescription for failure. After decades of neglect, the strategic significance of the Northern Flank is now receiving serious attention from NATO planners. Briefly put, control of the Norwegian Sea and the airfields in north Norway and Iceland could enable Soviet submarines and naval aviation to interdict NATO sea lines of communication (SLOCs) in time of war--potentially a war-winning strategy. Published in Parameters, p24-37, Jun 1989.